Pengaruh Skeptisme, Pengalaman Auditor, dan Self Efficacy Terhadap Audit Judgement Pada Kantor Akuntan Publik di Medan - Vera Yowanda; Vini Kristina; Riki Pernando; Sherly Sherly; Erika Erika; Wilsa Road Betterment Sitepu; Rika Dinarianti (Jurnal Ilmiah ESAI, 2019)
Judgment audit is a consideration made by public accountants in making an audit plan, and before issuing an opinion on the company's financial statements. The independent variables of this study are skepticism, auditor experience, and self efficacy. The dependent variable of this study is judgment audit. The purpose of this study is to examine and analyze the influence of skepticism, auditor experience, and self efficacy on judgment audits at the Public Accountant Office in Medan. This research uses descriptive quantitative research methods with the nature of research of causal relationships. The data were collected with questionnaires which were tested for validity and reliability before conducting the research. The test equipment used is normality test, multicollinearity test, and heteroscedasticity test. This study uses purposive sampling with a total of 90 respondents in the Public Accountant Office in Medan. The results of the study on the hypothesis indicate that skepticism, auditor experience, and self efficacy partially and simultaneously influence the judgment audit on the Public Accounting Firm in Medan. The conclusion of this study shows that skepticism, auditor experience, and self-efficacy have a positive and significant effect on judgment audits at the Public Accountant Office in Medan.Keywords: Skepticism, Auditor Experience, Self Efficacy, Audit Judgment